An exome sequencing based approach for genome-wide association studies in the dog. Issue 1 (December 2017) - Broeckx, Bart; Derrien, Thomas; Mottier, Stéphanie; Wucher, Valentin; Cadieu, Edouard; Hédan, Benoît; Le Béguec, Céline; Botherel, Nadine; Lindblad-Toh, Kerstin; Saunders, Jimmy; Deforce, Dieter; André, Catherine; et al.
Abstract Genome-wide association studies (GWAS) are widely used to identify loci associated with phenotypic traits in the domestic dog that has emerged as a model for Mendelian and complex traits. However, a disadvantage of GWAS is that it always requires subsequent fine-mapping or sequencing to pinpoint causal mutations. Here, we performed whole exome sequencing (WES) and canine high-density (cHD) SNP genotyping of 28 dogs from 3 breeds to compare the SNP and linkage disequilibrium characteristics together with the power and mapping precision of exome-guided GWAS (EG-GWAS) versus cHD-based GWAS. Using simulated phenotypes, we showed that EG-GWAS has a higher power than cHD to detect associations within target regions and less power outside target regions, with power being influenced further by sample size and SNP density. We analyzed two real phenotypes (hair length and furnishing), that are fixed in certain breeds to characterize mapping precision of the known causal mutations. EG-GWAS identified the associated exonic and 3′UTR variants within theFGF5 andRSPO2 genes, respectively, with only a few samples per breed. In conclusion, we demonstrated that EG-GWAS can identify loci associated with Mendelian phenotypes both within and across breeds.